2017
DOI: 10.4103/jnrp.jnrp_64_17
|View full text |Cite
|
Sign up to set email alerts
|

Single Parietal Burr-hole Craniostomy with Irrigation and Drainage for Unilateral Chronic Subdural Hematoma in Young Adults <40 Years: A Rationale behind the Procedure

Abstract: Background:Chronic subdural hematoma (CSDH) is one of the most common neurosurgical conditions. It is mostly a disease of elderly population with very little data about the young patients. There is also the debate regarding treatment strategies. We decided to determine the overall efficacy of the single burr-hole craniostomy (SBHC) for unilateral CSDH in young adults <40 years.Subjects and Methods:We performed a retrospective study of young patients undergoing SBHC for unilateral CSDH between January 2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[14] Most of the studies found the value of irrigation in reducing the RR of CSDH after burr-hole evacuation. [18,25,26] To the best of my knowledge, the present study is the first study that found 0% RR after surgical evacuation of CSDH within a relatively long follow-up period of at least 12 months. This study tried to emphasize that we have to perform certain combined operative steps to get better results in the surgical management of CSDH.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…[14] Most of the studies found the value of irrigation in reducing the RR of CSDH after burr-hole evacuation. [18,25,26] To the best of my knowledge, the present study is the first study that found 0% RR after surgical evacuation of CSDH within a relatively long follow-up period of at least 12 months. This study tried to emphasize that we have to perform certain combined operative steps to get better results in the surgical management of CSDH.…”
Section: Discussionmentioning
confidence: 55%
“…Most of the studies found the value of irrigation in reducing the RR of CSDH after burr-hole evacuation. [182526]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CSDH is a common neurosurgical condition, still, there is no consensus on the best surgical steps among different neurosurgical centers and among neurosurgeons of the same center such as the number of burr holes or their size [22,23], the use of irrigation [24], the site of the drain whether subdural or subgaleal, and the opening of the hematomas' inner membrane.…”
Section: Discussionmentioning
confidence: 99%